2010
DOI: 10.2298/gensr1002323m
|View full text |Cite
|
Sign up to set email alerts
|

Production characteristics of different malting barley genotypes in intensive nitrogen fertilization

Abstract: Two-year trials have been conducted in Technological Research Center in Zajecar. Research objects were six malting barley genotypes. The experimental crop was top dressed with the following amounts of nitrogen: 40, 60, 80 and 100 kg ha-1. The control variant was not top dressed. The obtained results showed that the genotypes reacted significantly to the increased amounts of nitrogen by changing their production characteristics and seed quality. In addition, the genotypes demonstrated certain varietal differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The issue regarding an optimal nitrogen rate remains a topical subject in numerous studies (Malešević et al, 2010;El Metwally et al, 2010;Janković et al, 2011;Magliano et al, 2014;Tanaka and Nakano, 2019).…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue regarding an optimal nitrogen rate remains a topical subject in numerous studies (Malešević et al, 2010;El Metwally et al, 2010;Janković et al, 2011;Magliano et al, 2014;Tanaka and Nakano, 2019).…”
Section: Results and Discusionmentioning
confidence: 99%
“…To provide good quality raw material for the beer industry, barley grains should be uniform in size, with the absolute weight of over 40 g and total protein below 12% (Malešević et al, 2010). One of the main tasks of a barley breeding programme is to increase barley productivity while preserving and improving grain quality (Valcheva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also effective in improving the yield of wheat components such as biochemical reactions, photosynthesis intensity, growing period, and accumulating dry matter in the shoots. However, excessive use of thresholds has a negative effect on barley grain quality [ 89 ]. The results showed that not all barley chromosomes played a role in low-temperature tolerance, which is consistent with the Li et al study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…74 and 1.63% in 2012, 2013 and 2014, respectively. The highest difference in the first year may be due to plant lodging at increased nitrogen rates (the correlation coefficient r = 0.721, P < 0.01), whereas the considerably smaller differences in the second year were attributed to the increased protein concentration under all nitrogen treatments due to drought and high temperatures during ripening. Numerous studies have reported the effect of applied N fertiliser at differing rates and timing on malting barley grain yields (Ramos et al 1995;Ruiter and Brooking 1996;Małecka and Blecharczyk 2008;Malešević et al 2010;Janković et al 2011;Shafi et al 2011;Křen et al 2014;Tahir et al 2019).…”
Section: Discussionmentioning
confidence: 99%